INTERJECTIONS IN THE INDONESIAN COMIC SERIES NEXT G AND THE DUTCH COMIC SERIES Kik - Dewi, Ni Wayan Putri Shanty; Djarwo, Andrea Pradsna Paramita (International Review of Humanities Studies, 2019)
Interjections are the words frequently found in both Indonesian and Dutch comic books. This study focuses on the types of interjection that have meaning and express feelings in a comic series published in Indonesia, Next G. This study aims to describe the types of interjection that express feelings in the comic series Next G in terms of the number and the syllable pattern and explains other characteristics of the use of interjection in the comic series. The method used in this study is descriptive qualitative using literature review as its data collection technique obtained from the comparison of the analysis and the interjection (Haeseryn, 1997) in the Dutch comic book Kik. The result of the study shows that the interjections that express feelings in the comic Next G and the comic Kik are similarly dominated by fear and the highest number of syllable consists of one to two syllables The functions of the interjection in both comic series are similar, to add excitement and to express strong emotions to the story. The use of interjections that comes from foreign languages can be found more in the Indonesian comic series Next G compared to the Dutch comic series Kik.